1985
DOI: 10.1083/jcb.101.3.1059
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor and heparin-like glycosaminoglycans regulate thrombospondin synthesis and deposition in the matrix by smooth muscle cells.

Abstract: Platelet-derived growth factor (PDGF), a smooth muscle cell (SMC) mitogen, and heparin-like glycosaminoglycans, known inhibitors of SMC growth and migration, were found to regulate thrombospondin synthesis and matrix deposition by cultured rat aortic SMC. The synthesis and distribution of thrombospondin was examined in growth-arrested SMCs, in PDGF-stimulated SMCs, and in heparin-treated SMCs using metabolic labeling and immunofluorescence techniques. Thrombospondin synthesis in response to purified PDGF occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
1
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(164 citation statements)
references
References 75 publications
8
154
1
1
Order By: Relevance
“…Perlecan is widely expressed in the basement membranes of adult tissues and in all vascular structures (Couchman, 1987;Murdoch et al, 1994) and has been directly implicated as a potent endothelial cell-derived inhibitor of SMC replication (Benitz et al, 1990). Our data indicate that at least some of the gene-regulating activity of perlecan resides in its heparan sulfate side chains, consistent with a large body of evidence implicating heparin-like molecules in the regulation of various SMC functions (Clowes and Karnovsky, 1977;Castellot et al, 1981;Majack and Bornstein, 1984;Majack and Clowes, 1984;Marcum and Rosenberg, 1984;Majack et al, 1985;Fritze et al, 1985;Benitz et al, 1990;Campbell et al, 1992;Pukac et al, 1992;Au et al, 1993).…”
Section: Role Of Basement Membrane Components Insupporting
confidence: 70%
“…Perlecan is widely expressed in the basement membranes of adult tissues and in all vascular structures (Couchman, 1987;Murdoch et al, 1994) and has been directly implicated as a potent endothelial cell-derived inhibitor of SMC replication (Benitz et al, 1990). Our data indicate that at least some of the gene-regulating activity of perlecan resides in its heparan sulfate side chains, consistent with a large body of evidence implicating heparin-like molecules in the regulation of various SMC functions (Clowes and Karnovsky, 1977;Castellot et al, 1981;Majack and Bornstein, 1984;Majack and Clowes, 1984;Marcum and Rosenberg, 1984;Majack et al, 1985;Fritze et al, 1985;Benitz et al, 1990;Campbell et al, 1992;Pukac et al, 1992;Au et al, 1993).…”
Section: Role Of Basement Membrane Components Insupporting
confidence: 70%
“…Both platelet-derived growth factor (PDGF) and transforming growth factor-␤ (TGF-␤) have been shown to induce TSP-1 secretion from vascular smooth muscle cells (VSMCs). 11,12 TSP-1 mRNA levels have been shown to be similarly regulated. Basic fibroblast growth factor upregulates TSP-1 mRNA in 3T3 cells, 13 and PDGF induces upregulation in a manner similar to that of c-myc and c-fos, with TSP-1 being classified as an immediate early response gene.…”
mentioning
confidence: 84%
“…Earlier studies have demonstrated an increased TSP-1 expression in response to serum, PDGF, and TGF-␤ in rat SMCs. [31][32][33][34] These differences might be due to several factors. (1) It is known that at least mouse and human TSP-1 promotor regions differ in their transcription factor binding sites and their serum responsive elements.…”
Section: Discussionmentioning
confidence: 99%
“…(1) It is known that at least mouse and human TSP-1 promotor regions differ in their transcription factor binding sites and their serum responsive elements. 16,35 (2) In the work by Majack et al, [31][32][33] mostly PDGF and TGF-␤ isolated from platelets were used, which might contain a mixture of different growth factor isoforms (eg, PDGF-AA, -AB, and -BB) and might also be contaminated by other growth factors (purity was Ͼ95%). In the study by Hugo et al, 34 the source of PDGF-BB was not mentioned.…”
Section: Discussionmentioning
confidence: 99%